Diving Deeper on Their Realms: The Prominence of Education on Street Children - Alexis Jewel L. Bermudez; Christian Paul G. Abalos; Christian Angelo L. Aguilar; Finlay Whea H. Campos; Jane P. Rempillo; Adonis S. Besa; Hassanal P. Abusama (Universitas Pendidikan Indonesia (UPI), 2021)
This study looks at the lives of children after accessing education, the assistance provided, and the efficiency of education at the heart of the classroom. This study aims to answer the following questions about street children: (i) How can they go to school and learn despite the challenges of being street children?; (ii) What programs are available to help them?; (iii) To what extent can these programs be provided to children?; and (iv) When taking to the streets. This study used a qualitative method by conducting interviews with five children aged 10-15 years who came from the city of Tacurong, the Philippines. Some street children continue their education despite all their limitations, some other children take to the streets to find additional money with the knowledge of their parents, and the amount of money they bring home is barely enough or only sufficient, and some programs reach those who are less able. In short, street children are aware of the importance of learning, they have dreams and many are trying to achieve them in any way they can - even if it means risking their lives to beg for alms on the streets. Since this study proves how important education is for these children, this study provides a better scope for us to look at children that are roaming the streets to achieve their dreams and programs.